DALAM UPACARA PERKAWINAN ADAT PADA MASYARAKAT MANNA BENGKULU SELATAN - Yunita Christantiawati (Saraswati)
It examines the "Dance Andun Function In Traditional Marriage Ceremony At Manna Society of South Bengkulu". Andun dance is dance in South Bengkulu most recognized by the public. Dance Andun generally always exist in every marriage ceremony customary communities Manna South Bengkulu, then dance Andun such is a major characteristic of the implementation of the customary marriage.Dance Andun presented in Customary marriage ceremony in South Bengkulu, its implementation is presented in time and show different names, namely 1) Dance Andun presented in Gegerit Night event, which is served at 20:00 pm, 2) Dance Andun presented in Nari Numbak Kebau event is held at 07.00 am, and 3) Dance Andun presented in Nari Palak Tanggau event, which is served at 12.00 pm. Of the three structures in the presentation of dance nuptial Indigenous Andun, each having different functions. Dance Andun held at the bride Gegerit Night function as a farewell to his friends, as a binder solidarity, as a means of intercommunication young people in South Bengkulu. In the event Nari Numbak Kebau Andun dance serves as the utterance of gratitude to Almighty God for having the implementation of the marriage ceremony, while in case of Nari Palak Tanggau Andun dance serves as notice that the bride had become a legitimate and has officially become a member of their family and the shift status social of a bride and groom and their extended family.Keywords: dance Andun, Serawai, custom undecided